2013
DOI: 10.1097/naq.0b013e3182a2fa15
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Manager Engagement

Abstract: The findings have implications for overcoming barriers that affect staff nurse engagement, improving outcomes, and creating definitions of nurse manager engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Kantek and Kaya (2017) determined that the nurses with administrative duties had a high level of professional values. It is stated in the literature that having professional values is essential for administrative nurses to evaluate and improve the quality of care and has an important role in developing the nursing culture of the institution (Gray and Shirey, 2013;Hendel and Gefen-Liban, 2003). In this study, it was found that the professional values of female nurses working in shifts and on-call had relatively lower professional values than those working on day shifts, but it was not a significant difference.…”
Section: Discussionmentioning
confidence: 57%
“…Kantek and Kaya (2017) determined that the nurses with administrative duties had a high level of professional values. It is stated in the literature that having professional values is essential for administrative nurses to evaluate and improve the quality of care and has an important role in developing the nursing culture of the institution (Gray and Shirey, 2013;Hendel and Gefen-Liban, 2003). In this study, it was found that the professional values of female nurses working in shifts and on-call had relatively lower professional values than those working on day shifts, but it was not a significant difference.…”
Section: Discussionmentioning
confidence: 57%
“…Nursing and workplace engagement concepts are profoundly intertwined and influence a nurse's commitment to an organization, and the nursing profession, while maintaining a positive and fulfilling state of mind characterized by vigor and dedication. 1 Engaged employees are highly motivated, committed, and dedicated to achieving their goals and the goals of the organization. [2][3][4] It is essential in promoting employee satisfaction, maintaining high-quality patient care, and improving the nursing profession.…”
Section: An Integrative Reviewmentioning
confidence: 99%
“…9 Research has identified that many leaders become disengaged because of a lack of formalized orientation program that focuses on role preparation and organizational culture, thus facilitating the successful transition into leadership roles by improving knowledge and confidence. 1,10,11 The American Organization for Nursing Leadership developed a domain framework that outlines guiding principles for skills, knowledge, and abilities in which nursing leaders must gain expertise to succeed in their role. 12,13 If new nursing leaders are not successfully transitioned into their new roles, there may be unexpected negative outcomes including leader and staff retention, nursing quality of care, and patient experience outcomes.…”
Section: An Integrative Reviewmentioning
confidence: 99%